Properties, Processing and Applications of Glass and Rare Earth-Doped Glasses for Optical Fibres. Vol. PM82 - Hewak, D. W. (Institution of Engineering & Technology Books International, Inc. [distributor], 1998)
Annotation An authoritative, encyclopedic reference source for researchers and engineers interested in R & D into optical fibers.
Keywords: elektronické knihy; electronic books